Provisional Application of Treaties: The EU's Contribution to the Development of International Law. (18th September 2020) - Chamon, Merijn
Abstract: Provisional application has become a quasi-automatic corollary to the signature of mixed bilateral European Union (EU) agreements. Resort to provisional application is thereby informed by a rationale hitherto unknown in international law: it allows federal polities where the federal level does not have exclusive treaty making powers to develop an effective external action that is not hindered by that polity's complex internal division of competences. This article argues that the EU has also developed a rather consistent practice in relation to provisional application. The EU thereby distinguishes between its treaty partners whereby some of them simply agree that the EU unilaterally determines the scope of provisional application. Because of the reference to the EU's internal division of competence, the internal law of the parties, something that is typically not relevant under international law, acquires legal significance. The EU's practice is found to be largely in line with the Draft Guidelines on Provisional Application that are being elaborated by the International Law Commission, although clearly it is also more refined on some points. Lastly, the article identifies one pressing issue which requires clarification, and which is not properly addressed in the Draft Guidelines. That is the question on the fate of the provisional application by the EU of part of a mixed agreement where one individual EU member state has decided not to ratify that agreement.